Splenorenal shunt for reconstruction of the gastric and splenic venous drainage during pancreatoduodenectomy with resection of the portal venous confluence - Saeedi, Mohammed al; Frank-Moldzio, Leonie; Contin, Pietro; Mayer, Philipp; Loos, Martin; Schmidt, Thomas; Schneider, Martin; Müller, Beat P.; Berchtold, Christoph; Mehrabi, Arianeb; Hackert, Thilo; Büchler, Markus W.; et al. (Langenbeck's archives of surgery, 2021)
Resection of the portal venous confluence is frequently necessary for radical resection during pancreatoduodenectomy for cancer. However, ligation of the splenic vein can cause serious postoperative complications such as gastric/splenic venous congestion and left-sided portal hypertension. A splenorenal shunt (SRS) can maintain gastric and splenic venous drainage and mitigate these complications.